Tobalu's Gratitude After the Rambu Solo Traditional Funeral in Pattan Ulusalu Village - Pasalli, Ravael Angga (Journal of Social Research, 2023)
Rambu Solo is a unique funeral ritual that originated from Toraja. Ritual Rambo solo in each native region of Toraja is different. One of the unique things is that after the ritual of the customary Rambu Solo ceremony carried out a few days later a thanksgiving ceremony will be held and this only happens in the Pattan Ulusalu Kelurahan area. Accordingly, this study aims to find out the image of gratitude to Tobalu after the funeral ceremony of the Rambu Solo in Pattan Ulusalu Kelurahan. The type of research used by the researchers in this research is the type of qualitative research method with observation and an integral approach to the background of the research subject. The aim of the researchers using qualitative research methods with observation and integrity approach on the background of the subject of research is to be able to describe the phenomenon that exists in Pattan Ulusalu Kelurahan related to the picture of the gratitude of Tobalu after the activities of the customary funeral ceremony of Rambu Solo. Participants in the study were two widows who had been left dead by their husbands and had performed a customary burial ceremony, Rambu Solo. The data from this study was obtained through interviews and observation techniques. The results of the research found that there was self-acceptance on Tobalu who had performed the funeral ceremony of Rambu Solo against her husband. Self-acceptance arises through gratitude that is then expressed through activities and activities as usual.